APEX journey towards a sustainable future - Abd Razak, Dzulkifli (2010)
UNIVERSITI Sains Malaysia (USM) "celebrated" its first anniversary of being conferred the APEX (Accelerated Programme for Excellence) status last year. This highly innovative initiative, which was launched as a component of the National Higher Education Strategic Plan in 2007, saw USM adopting a new vision statement Transforming Higher Education for a Sustainable Tomorrow. This, in part, is the result of a Scenario Planning exercise undertaken by the university in 2005 which lasted for about 18 months.